Bond Strength of New Fiber Post-system (Rebilda GT) - Alkhalidi, Emad Farhan; Ahmad, Zena A. (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this in vitro study is to determine the push-out bond strength of bundle glass fiber post (Rebilda GT) and tapered glass fiber post (Rebilda fiber post). MATERIALS AND METHODS: Twenty freshly extracted human single rooted premolar teeth were used, all teeth were endodontically treated, after 24 h from obturation the gutta-percha removed leaving 5 mm apically to ensure clinically acceptable apical seal. Finally, all canals were flushed with 2 ml NaOcl 5.25% and 2 ml distilled water, respectively, then the canals were dried using paper points. The roots were divided randomly into two sets with ten roots for each group according to post-type. Group A: Rebilda fiber posts were used. Group B: Rebilda GT bundle fiber posts were used. The posts were inserted into the canals according to the manufacturer instructions. All specimens were stored for 72 h in an incubator. Slices of 2 mm thickness were cut from the roots at different levels (cervical, middle, and apical thirds), bond strength was determined using universal testing machine at a speed of 0.5 mm/min. RESULTS: One-way analysis of variance and Tukey HSD tests showed that the (bundle fiber) Rebilda GT fiber post had bond strength higher than that of the Rebilda fiber post in all regions. (p < 0.05), also the cervical area showed higher bond strength in both groups than the middle and the apical areas, respectively. CONCLUSIONS: The bundle glass fiber post (Rebilda GT) showed bond strength higher than the taper glass fiber (Rebilda fiber) post in all regions (apical, middle, and cervical). The cervical region showed higher bond strength than the middle and the apical thirds.